2022
DOI: 10.1155/2022/3081523
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Network Information Technology in Physical Education and Training System under the Background of Big Data

Abstract: During the last two decades, rapid development in the network technology has been observed, particularly hardware, and the development of software technology has accelerated, resulting in the launch of a variety of novel products with a wide range of applications. Traditional sports training systems, on the other hand, have a single function and a complex operation that cannot be fully implemented in colleges and universities, causing China's sports training to stagnate for a long time. The goal of physical ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Physical education is a very important subject studied in schools (Green, 2014;Stormoen et al, 2016), as it makes a significant contribution to the spiritual, moral, social, and cultural development (Cale et al, 2016;Harris, 2018) and the development of students (Akhter & Ahmed, 2021). The traditional mode of teaching physical education is gradually being abandoned, and physical education has begun to change direction towards intelligent forms (Ding et al, 2021;Meng, 2021;Yu, 2021), such as the use of MOOCs in physical education learning at the higher education level in football materials (Tian et al, 2022), basketball learning through network information technology through images, words, sounds, videos, and animations (Chen & Zhou, 2022), procurement of smart sports in universities as a resource for smart sports teaching, smart sports facilities, online competitions, and virtual sports for college students (Deng et al, 2022), and the use of AI and metaverse through the mobile internet (Li et al, 2022). In addition, the development of the Internet of Things for physical education teaching towards smart forms can also be observed, especially during the COVID-19 pandemic, and proven to help in online learning (Bucea-Manea-Țoniș et al, 2022), by being oriented towards actual classroom teaching (Cai et al, 2019;Nosova et al, 2015;Turton et al, 2016), such as the use of Google Classroom, Moodle, and other information technology (Shmeleva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Physical education is a very important subject studied in schools (Green, 2014;Stormoen et al, 2016), as it makes a significant contribution to the spiritual, moral, social, and cultural development (Cale et al, 2016;Harris, 2018) and the development of students (Akhter & Ahmed, 2021). The traditional mode of teaching physical education is gradually being abandoned, and physical education has begun to change direction towards intelligent forms (Ding et al, 2021;Meng, 2021;Yu, 2021), such as the use of MOOCs in physical education learning at the higher education level in football materials (Tian et al, 2022), basketball learning through network information technology through images, words, sounds, videos, and animations (Chen & Zhou, 2022), procurement of smart sports in universities as a resource for smart sports teaching, smart sports facilities, online competitions, and virtual sports for college students (Deng et al, 2022), and the use of AI and metaverse through the mobile internet (Li et al, 2022). In addition, the development of the Internet of Things for physical education teaching towards smart forms can also be observed, especially during the COVID-19 pandemic, and proven to help in online learning (Bucea-Manea-Țoniș et al, 2022), by being oriented towards actual classroom teaching (Cai et al, 2019;Nosova et al, 2015;Turton et al, 2016), such as the use of Google Classroom, Moodle, and other information technology (Shmeleva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%